IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF STAD MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR TEKNIK DASAR PASSING CONTROL SEPAKBOLA - I Dewa Nyoman Arimbawa .; Drs. I Made Danu Budhiarta,M Pd. .; Kadek Yogi Parta Lesmana, S.Pd.,M.Pd . (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan Undiksha, 2016)
Penelitian ini bertujuan untuk meningkatkan aktivitas dan hasil belajar teknik dasar passing control sepak bola melalui implementasi model pembelajaran kooperatif tipe STAD pada siswa kelas VIII I SMP Negeri 1 Banjar tahun pelajaran 2015/2016. Penelitian ini tergolong penelitian tindakan kelas dengan bentuk guru sebagai peneliti, yang dilaksanakan dalam dua siklus dan setiap siklus terdiri dari dua kali pertemuan. Subjek penelitian ini adalah 30 orang, terdiri dari 15 orang putra dan 15 orang putri, yang dianalisis menggunakan analisis statistik deskriptif. Berdasarkan analisis data aktivitas belajar pada observasi awal siswa aktif 4 orang (13,3%), setelah diberikan tindakan pada siklus I, siswa aktif meningkat menjadi 13 orang (43,33%), setelah pemberian tindakan pada siklus II, siswa aktif meningkat menjadi 28 orang (93,3%). Sedangkan berdasarkan analisis data hasil belajar siklus I pada aspek sikap siswa tuntas 13 orang (43,33%), pada aspek pengetahuan siswa tuntas 20 orang (66,7%), dan pada aspek keterampilan siswa tuntas 16 orang (53,3%). Sedangkan siklus II pada aspek sikap siswa tuntas 30 orang (100%), aspek pengetahuan siswa tuntas 30 orang (100%), dan aspek keterampilan siswa tuntas 28 orang (93,3%). Berdasarkan hasil analisis data, simpulan penelitian ini adalah aktivitas dan hasil belajar teknik dasar passing control sepak bola meningkat melalui implementasi model pembelajaran kooperatif tipe STAD pada siswa kelas VIII I SMP Negeri 1 Banjar tahun pelajaran 2015/2016. Disarankan kepada guru penjasorkes agar dapat mengimplementasikan model pembelajaran kooperatif tipe STAD karena dapat meningkatkan aktivitas dan hasil belajar teknik dasar passing control sepak bola siswa. Kata Kunci : Kooperatif, aktivitas, hasil belajar, sepak bola. This study aims to improve the activity and results ofthe basic techniques’ learningof football’s passing controlthrough the implementation of cooperative learning model STAD at grade VIII of SMP Negeri 1 Banjar in academic year 2015/2016. This research is classified as a class action research which was the teacher as researcher and it was conducted in two cycles that each cycle consisting of two meetings. The subjects were 30 students, consisting of 15 male and 15 female, were analyzed using descriptive statistical analysis. Based on the first observation, the analysis of students’ activity show that there was 4 (13.3%) students actively, after being given the action on the first cycle, the students who being actively was increased to 13 (43.33%)students, then on the second cycle, there was 28 (93.3%)students became actively. Whereas, based on the data analysis of students’ attitude outcomes in the first cycle show that there was passed by 13 (43.33%) students only, in the ability of students’ knowledge was completed by 20 (66.7%) students, and there was 16 (53.3%) students who got completelyin the aspect of skill. While in the second cycle show that in the aspect of attitudes there was all of students got completely, that was30 (100%), then in the aspects of knowledge students who got completely became 30 (100%) students, and in the aspects of skills there was 28 (93.3%) students who got completely. Based on the result of the data analysis, it can be concluded that the result of the basic techniques’ learning of football’s passing controlwas increased by the implementation of cooperative learning model STAD at grade VIII of SMP Negeri 1 Banjar in academic year 2015/2016. So that, it is recommended to the Penjasorkes’teachers in order to implement the cooperative learning model STAD because it can be increasing the activity and results of students’ learning in basic techniques of football’s passing control. keyword : Cooperative, activities, learning outcomes, football.